Behaviour of grout-filled double-skin steel tubular T-joint subjected to low-velocity impact. (November 2019) - Li, Wei; Gu, Ying-Zhuo; Han, Lin-Hai; Zhao, Xiao-Ling
Abstract: The grouted T-joint in offshore structure is usually subjected to low-velocity impact caused by ship collision. The behaviour of these joints under lateral impact loading is investigated. Tests on 12 specimens including eight grouted T-joints are conducted. The composite T-joint consists of grout-filled double-skin steel tubular chord and hollow steel section brace. The constant axially compressive load is applied along the axis of the composite chord and the impact load is applied along the axis of the hollow steel tubular brace. A finite element model is established and verified. The influences of various parameters on the T-joint behaviour are discussed. Highlights: We provide new test data of the impact behaviour of the T-joint consisted of GFDST chord and hollow steel brace. We establish the FE model to simulate the impact performance of GFDST T-joint. We discuss effects of grout and other key parameters on the impact performance of GFDST T-joint.